Ekstrak secang berukuran nano dengan kaolin sebagai pembawa - Irmanida Batubara; Zaenal Abidin; Min Rahminiwati (Jurnal Ilmu Pertanian Indonesia, 2011)
Sappanwood extracts reported had antiacne activity with brazilin as active component. To develop antiacne formula from sappanwood extract, nanoparticle sappanwood with kaolin nanosize as carrier was developed. Carrier used was montmorillonite yellow, brown montmorillonite, yellow kaolin from Cicalengka, white kaolin from Cicalengka, kaolin from Bangka Belitung, and kaolin from Wonosari. The best carrier for active components of Sappanwood was selected based on UV-Vis spectroscopy, thin layer chromatography, liquidchromatography tinggi.dan performance antijerawat activity test. The most potent kaolin as Sappanwood carrier was kaolin from Bangka Belitung with percent inhibiton of DPPH scavenging reaction about 78% at 50 mg kaolin.